Integrating Local Culture into Digital Learning Media for Elementary School Students in Border Regions - Tri Syamsijulianto; Alvira Pranata (Jurnal Profesi Pendidikan, 2025)
This study aims to integrate local cultural values into digital learning media for elementary school students in border areas, to enhance artistic and civic literacy. The development used the Design and Development Research (DDR) approach with the ADDIE model: Analysis, Design, Development, Implementation, and Evaluation. The study was conducted in Entikong District, West Kalimantan, involving fourth-grade teachers and students from four elementary schools. Data were collected through observations, interviews, questionnaires, validation sheets, and Focus Group Discussions (FGD). The result shows that the integration of local culture into the “Go Buya” digital learning media effectively enhances students’ understanding of local traditions, cultural diversity, and civic values. The media demonstrated high feasibility in terms of content, design, and user engagement. Learning outcomes increased significantly after using the media, as indicated by improved post-test results and positive responses from students and teachers. The findings suggest that incorporating local culture into digital learning media can foster meaningful learning experiences, particularly for border-area students who face limited access to culturally relevant educational materials.